Total Chemical Synthesis of Modified Histones - Qi, Yun-Kun; Ai, Hua-Song; Li, Yi-Ming; Yan, Baihui (Frontiers in Chemistry, 2018)
In the post-genome era, epigenetics has received increasing attentions in recent years. The post-translational modifications (PTMs) of four core histones play central roles in epigenetic regulation of eukaryotic genome by either directly altering the biophysical properties of nucleosomes or by recruiting other effector proteins. In order to study the biological functions and structural mechanisms of these histone PTMs, an obligatory step is to prepare a sufficient amount of homogeneously modified histones. This task cannot be fully accomplished either by recombinant technology or enzymatic modification. In this context, synthetic chemists have developed novel protein synthetic tools and state-of-the-art chemical ligation strategies for the preparation of homologous modified histones. In this review, we summarize the recent advances in the preparation of modified histones, focusing on the total chemical synthesis strategies. The importance and potential of synthetic chemistry for the study of histone code will be also discussed.